Bridging the Protection Gap: Strategic Approaches, Barriers, and Inclusive Market Growth in Tanzania’s Insurance Sector - Kawoloka, Manasseh Barak (Digital Repository of Theses, 2025)
Despite sustained regulatory reform and increasing policy focus on financial inclusion, Tanzania’s commercial insurance sector continues to exhibit low penetration and limited engagement with underserved populations. The protection gap, defined as the difference between insured and total economic losses, remains wide in Africa, including Tanzania. According to Swiss Re Institute (2021), nearly 70 per cent of global economic losses are uninsured, with Africa representing one of the most underinsured regions globally. This doctoral study investigates how insurance companies in Tanzania strategically respond to structural constraints, socio-cultural barriers, and regulatory frameworks in their efforts to increase market penetration and foster inclusive growth. Employing a mixed-methods approach, the research combines semi-structured interviews with 371 participants across the insurance ecosystem and a quantitative survey of 187 general public and MSME respondents. The findings reveal that while insurers are making incremental progress through digital innovations and partnership models such as bancassurance, these approaches often lack contextual adaptation and fail to address critical consumer concerns, particularly trust, product comprehension, and cultural acceptability. The study identifies a deep misalignment between regulatory intent, provider strategy, and end-user experience. Logistic regression and correlation analyses confirm that psychological and informational factors; rather than purely economic constraints; are the most influential predictors of insurance uptake. The research integrates these findings through a conceptual synthesis aligned with Institutional Theory and the Dynamic Capabilities framework, culminating in an actionable, stakeholder-informed model for strategic realignment. It recommends community-based outreach, culturally tailored products (including Takaful), digital distribution enhancement, and policy co-creation as key levers for bridging the protection gap. The thesis contributes to academic theory and policy practice by presenting an integrated framework for inclusive insurance development in low-penetration markets. Keywords: Insurance Penetration; Financial Inclusion; Tanzania; Strategic Adaptation; Trust; Takaful; Dynamic Capabilities; Institutional Theory; Mixed Methods; Inclusive Growth.